A Study on Peak-to-Average Power Ratio in DWT-OFDM Systems - Filbert Hilman Juwono; Randy S. Putra; Dadang Gunawan (Institute of Advanced Engineering and Science, 2014)
Orthogonal frequency division multiplexing (OFDM) systems suffer from large peak-to-average power ratio (PAPR). In this paper we study the discrete wavelet transform (DWT)-based OFDM systems. In particular, we discuss the effect of the decomposition level of each wavelet family in the DWT-based OFDM regarding the PAPR. The simulation results show that, in general, there is a decomposition level that minimize the PAPR in every wavelet family. In addition, we also analyze the effect of clipping nonlinearities, i.e. conventional clipping and deep clipping, as PAPR reduction method in DWT-OFDM systems. The results show that the clipping nonlinearities give a noticeable PAPR reduction. However, as DWT-OFDM itself has lower PAPR compared to the conventional discrete Fourier transform (DFT)-based OFDM, the clipping nonlinearity subsystem may not be essential as it degrades the system performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5375